The Influence of Religion on Life Satisfaction in Italy - Ciziceno, Marco (Italian Sociological Review, 2021)
Italy is the cradle of Catholicism and, despite the secularization process, religion continues to be part of its national culture. Although Italian sociologists have investigated the religious paradigm in Italy, there are aspects of such phenomenon still little explored. This paper examines the potential influence religion has on individuals’ life satisfaction. Data from the European Value Study survey provides evidence of a two-way interaction between religion and life satisfaction, with a substantial effect only in the case of public religious forms. This association seems to be moved by the mechanism of social support, and it differs across Italian regions. Results confirm the hypothesis that in areas of Italy more exposed to social isolation religion is associated whit life satisfaction because, in those areas, religion supplies peoples’ need to belong. Further confirmation of this analysis came from the fact that in grey zones of “religious conformism” the influence of religion on life satisfaction is marginal.